A density result for homogeneous Sobolev spaces. (December 2021) - Nandi, Debanjan
Abstract: We show that in a bounded Gromov hyperbolic domain Ω smooth functions with bounded derivatives C ∞ ( Ω ) ∩ W k, ∞ ( Ω ) are dense in the homogeneous Sobolev spaces L k, p ( Ω ) .